Magnetic resonance imaging and arthroscopy of a discoid lateral meniscus in a dog - Ohlerth, S.; Lang, J.; Scheidegger, J.; Nötzli, H.; Rytz, U. (Veterinary and Comparative Orthopaedics and Traumatology, 2001)
For the first time in veterinary literature, magnetic resonance and arthroscopic features of a discoid lateral meniscus in a dog are described. A 15-monthold Labrador Retriever with a history of mild intermittent left hindlimb lameness was referred to our clinic. Physical examination revealed mild joint effusion of the left stifle and absence of a cranial drawer motion and tibial compression test. Survey radiographs demonstrated mild joint effusion and peri-articular new bone formation. Low-field magnetic resonance tomography of the left stifle joint demonstrated injury of the cranial cruciate ligament and a discoid lateral meniscus. Two weeks later, arthroscopy revealed a partial tear of the cranial cruciate ligament with mild synovitis. Furthermore, some fibres inserted abnormally cranial to the inter-meniscal and cranial tibial ligament of the medial meniscus. The lateral meniscus was discoid in shape. Subsequent arthrotomy confirmed the diagnoses. Discoid meniscus is a rare finding in the dog with unknown clinical relevance whereas it is well known in humans.A 15-month-old Labrador Retriever with mild left hindlimb lameness, mild joint effusion of the left stifle but without signs of stifle instability is presented in this report. Low-field magnetic resonance tomography demonstrated injury of the cranial cruciate ligament and a discoid lateral meniscus. Subsequent arthroscopy and arthrotomy confirmed these findings. A literature review on discoid meniscus in humans and in dogs is presented.
Keywords: Discoid meniscus; cranial cruciate ligament; MRI; arthroscopy; dog